The Mediating Role of Social Media Use and Perceived Value between Tourist Knowledge and Tourist Attitudes: A Study on the Digital Native Generation - Putu Gde Arie Yudhistira; Ni Made Dyah Ryana Kurniasari; Shabinna Putri Setyo Bambang (Universitas Airlangga, 2023)
Objective: This study examines the relationship between tourist knowledge and attitudes mediated by social media use and perceived value. Design/Methods/Approach: Data was collected using a questionnaire with a judgment sampling technique. A total of 358 participants from the Gen Z generation were chosen for the study. The data was analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) through outer and inner models, using SmartPLS 4. Findings: The research findings indicate that the level of tourist knowledge does not have a direct impact on their attitudes. However, it indirectly affects their attitudes through mediating factors such as social media use and perceived value. Originality: This research adopts the KAB (Knowledge Attitude Behaviour) theory and extends previous studies' results by adding mediation from the constructs of social media use and perceived value. This study aims to fill this gap by examining the relationship between tourist knowledge and attitudes toward visiting a destination while also investigating the mediating roles of perceived value and social media use. Practical/Policy implication: To promote knowledge and positive attitudes towards a destination, stakeholders must ensure that the perceived value remains excellent. It necessitates understanding the destination well and highlighting its unique value to visitors through attractions, prices, or other relevant variables. Therefore, to cultivate awareness and favorable opinions toward a destination, stakeholders must dedicate themselves to upholding its perceived value.